Particle Filtering-Based Low-Elevation Target Tracking With Multipath Interference Over the Ocean Surface - Shi, Xiaoran; Taheri, Abdolreza; Cecen, Tugba; Celik, Nurcin (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
As radar signals propagate above the ocean surface to determine the trajectory of a target, the signals that are reflected directly from the target arrive at the receiver along with indirect signals reflected from the ocean surface. These unwanted signals must be properly filtered; otherwise, their interference may mislead the signal receiver and significantly degrade the tracking performance of the radar. To this end, we propose a low-elevation target tracking mechanism considering the specular and diffuse reflection effects of multipath propagation over the ocean surface simultaneously. The proposed mechanism consists of a state-space model and a particle filtering algorithm and promises considerable improvements in the capacity and accuracy of the radar tracking systems. The efficiency and accuracy of the developed target tracking method are tested and compared with an unscented Kalman filtering method in two- and three-dimensional space using a series of simulation experiments.
Keywords: Low-elevation targets; multipath interference; particle filtering (PF); radar tracking; state-space model; RADAR; Engineering; Telecommunications